Childhood diabetes mellitus in Phra Nakhon Si Ayutthaya Hospital - Sitthisan, Manassaya (Journal of Preventive Medicine Association of Thailand, 2021)
Diabetes mellitus (DM) is a chronic disease that impacts the quality of life in any age, but there are no data of the attributes of childhood DM in Phra Nakhon Si Ayutthaya Hospital. Therefore, the purpose of this retrospective study was to describe the prevalence, type of DM, clinical presentation, laboratory data, treatment regimen, and complications, as well as to compare the attributes of Type 1 DM (T1DM) and Type 2 DM (T2DM). The sample comprised 34 children with diabetes, and the data were collected between October 1, 2015 to September 30, 2020, in the Outpatient Department. The results showed that the prevalence of childhood DM were 9.1 per 10,000 patients. There were 17 patients (50%) with T1DM, 15 patients (44%) with T2DM, and two patients (6%) with other types. Classical clinical DM was found in almost all of the T1DM patients, but the T2DM patients required blood screening or a urine test to conduct the diagnosis. A lower HbA1C level was found in the conventional insulin regimen group than the basal bolus regimen group in T1DM. In conclusion, the prevalence of childhood DM was slightly low. As such, a blood test would be required for the diagnosis of T2DM, especially in cases with obesity. Conventional insulin regimen had a lower HbA1c; thus, further research would be needed to determine the risk factors of poor glycemic control in patients undertaking the basal bolus regimen in T1DM.